Pendampingan Analisis Sistem Pemerintahan Daerah Kabupaten Probolinggo Berbasis Elektronik (SPBE) - M Noer Fadli Hidayat (GUYUB: Journal of Community Engagement, 2024)
The Indonesian government is focusing on the development of information and communication technology as a means to improve public services to the community. This is reflected in the issuance of the Electronic-Based Government System (EBS) guidelines. The Probolinggo District Government also implements good governance to improve the welfare of the community. In 2022, Probolinggo Regency has carried out an SPBE evaluation which resulted in an SPBE index value of 2.42 and received a Fair predicate. This Community Service (PkM) aims to analyze the aspects that have the lowest contribution to the evaluation of SPBE of the Probolinggo Regency Government. Several aspects of the SPBE assessment are presented as having the lowest contribution value which results in a lack of SPBE index value for the Probolinggo Regency Government. The aspect with the lowest contribution is located in the SPBE Governance domain, namely the SPBE Organizer aspect and is located in the SPBE Management domain, namely the SPBE Management Implementation aspect and the ICT Audit aspect. Each aspect has its own weaknesses as a measure of the low value obtained. Recommendations for improvement to increase the evaluation value in each aspect in the hope of building quality work in the Probolinggo Regency Government that is effective, efficient, and productive as well as harmonizing the SPBE architecture and SPBE plan map from the central government